THE USE OF CONJOINT ANALYSIS IN STRATEGIC DECISION MAKING: AN INITIAL STUDY - Anatan, Lina (KINERJA, 2018)
In an environment where change often comes through crises, disruptions and discontinuities, strategic decision making cannot be based on simple extrapolations of current situation. A firm can respond to crisis in variety of ways through strategy implementation, such as turnaround strategy, liquidation strategy, and end-games strategy which have different attributes. This initial study, focusing on Magister Management students as respondents, seeks to examine what strategy attributes and combination of strategy attributes are important to consider strategy implementation in crisis. To produce the combination of strategy attributes that effect respondentâ€™s decision making to choose a strategy in crisis, conjoint analysis is used in this study. The result shows the combination of strategy attributes such as risk, benefit, and policy are importants in affecting respondentâ€™s decision to implement strategy in crisis. Based on the statistical analysis, turnaround strategy which is reprenseted as reorganizational policy is the most preffered strategy to respon organizational crisis.Â